
[5xy^2(x^2-3xy)-(-3x^2y^2)^3]/(5xy^2)
4个回答
展开全部
[5xy^2(x^2-3xy)-(-3x^2y^2)^3]/(5xy^2)
=[5xy^2(x^2-3xy)+27x^6y^6]/(5xy^2)
=5xy^2(x^2-3xy)/(5xy^2)+27x^6y^6/(5xy^2)
=x^2-3xy+27x^5y^4/5
=[5xy^2(x^2-3xy)+27x^6y^6]/(5xy^2)
=5xy^2(x^2-3xy)/(5xy^2)+27x^6y^6/(5xy^2)
=x^2-3xy+27x^5y^4/5
展开全部
5-2√6
=3-2√6+2
=(√3-√2)²
所以√(5-2√6)=√3-√2
8-4√3
=6-2√12+2
=(√6-√2)²
所以2-√3=(8-4√2)/4=(√6-√2)²/4
所以√(2-√3)=(√6-√2)/2
=3-2√6+2
=(√3-√2)²
所以√(5-2√6)=√3-√2
8-4√3
=6-2√12+2
=(√6-√2)²
所以2-√3=(8-4√2)/4=(√6-√2)²/4
所以√(2-√3)=(√6-√2)/2
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
[5xy^2(x^2-3xy)-(-3x^2y^2)^3]/(5xy^2)
=(5x^3y^2-15x^2y^3+27x^6y^6)/5xy^2
=x^2-3xy+27x^5y^4/5
=(5x^3y^2-15x^2y^3+27x^6y^6)/5xy^2
=x^2-3xy+27x^5y^4/5
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询